QUIZIZZ: MEDIA GAMES UNTUK MENINGKATKAN PERHATIAN DAN HASIL BELAJAR MAHASISWA - Ayu Rahayu (LPPM STKIP PGRI Sidoarjo, 2023)
A good understanding of learning material is something that every student must have. Understanding is built through attention in listening to the material discussed in the learning process. Intense attention will produce good understanding so that later it will have a positive impact on learning outcomes. This study aims to determine the effect of using quizizz as media games on students' attention and learning outcomes. This type of research is quasi-experimental with a posttest-only design. The research sample is 30 students as the control class and 30 students as the experimental class. The instruments used were observation sheets to measure student attention and essay tests to measure learning outcomes. The percentage of student attention in the control class was 56.63% in the good category while the experimental class was 65.52% in the good category. The learning outcomes on the prerequisite test show that the data are normally distributed and homogeneous. Test the hypothesis with an independent sample t-test, namely the sig value (0.01) <0.05 so that it is stated that there is an effect of using Quizizz on increasing student attention and learning outcomes.